Combined effect of seawater and load on methacrylate adhesive. Issue 4 (April 2023) - Rodríguez-Dopico, Francisco J.; Carbas, R.J.C.; Borges, Catarina S.P.; Tarrío-Saavedra, J.; da Silva, L.F.M.; García, A.Álvarez
Abstract: Although the shipbuilding industry is constantly demanding new advanced joining solutions, adhesive technology is not as developed in the marine as compared to other industries. The main reason is the lack of specific knowledge that guarantees the durability of the bonded joints in optimal conditions during the life cycle of a ship. This work simulates in the laboratory a marine-like environment by immersing an adhesive in seawater and subjecting it to constant loading. The objective is to characterize the seawater absorption behavior and its consequences on the mechanical, thermal, and chemical properties of the adhesive after this aging process. Seawater ingress was determined through gravimetric tests at several load conditions of the tensile strength of the adhesive. Besides, absorption process was studied using Fick's Law, determining the diffusion coefficients. The thermal behavior was monitored with differential scanning calorimetry (DSC) and the chemical degradation was analyzed using Fourier transform infrared spectroscopy (FTIR). Also, the mechanical properties were determined by tensile tests. The surface of the adhesive (dried) was studied by Scanning Electron Microscopy (SEM) technique and the porosity was measured by physisorption with a high-performance adsorption analyzer. A numerical simulation was developed using Darcy's Law combined with continuity equation. The results show that application of loads and immersion in seawater until full saturation of seawater improve the mechanical properties of the adhesive, but it affects negatively to the glass transition temperature. This should be considered when designing adhesive bonding joints on ships. Graphical abstract: Image 1 Highlights: Loads accentuate reduction on glass transition temperature after aging in seawater. Darcy's and Fick's Law models are applied to study diffusion. Seawater diffusion behavior on adhesive under constant load is Fickian. Mechanical properties of adhesive improve with load after immersion in seawater. Poisson's ratio decreases as load condition increases during aging.